MONITORING TINGKAT PELANGGARAN TRAFFIC LIGHT DI JALAN RAYA MENGGUNAKAN MIKROKONTROLER DAN VISUAL BASIC NET - muhammad syahputra novelan (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2019)
Traffic light or what we call traffic lights is a device that functions to regulate the flow of vehicles on the road. However, as we know, there are still many vehicle users who violate the traffic light signs, especially in areas that lack supervision from the authorities so that many cause accidents or traffic jams. The number of accidents from year to year continues to grow. Congestion occurs everywhere, especially in big cities. One reason is the lack of tolerance between drivers and motorists. They overtook each other not to budge with one another and also not infrequently violated the traffic lights. The author here tries to create a system of monitoring the level of traffic light violations on the highway based on the ATmega16 microcontroller and also displays data on the number of traffic light violations with a graphical display on the computer. Not all objects can be detected accurately and directly, depending on the level of a vehicle. To be able to implement a traffic light monitoring system accurately, we need a communication system and display that is appropriate, reliable and accurate, so that data on violations that occur can be sent accurately and realtime and can be directly observed. Keywords : Monitoring, GUI, Photodiode, Microcontroller, LED, LCD